Synchronization of complex networks with impulsive control involving stabilizing delay. Issue 8 (May 2020) - He, Xinyi; Peng, Dongxue; Li, Xiaodi
Abstract: This paper mainly investigates the globally exponential synchronization of complex networks (CNs) via delayed impulsive control, where the stabilizing effects of time-delay in impulses are fully considered. Based on Lyapunov method and average dwell-time (ADT) approach, sufficient conditions are proposed to deal with the synchronization problem of CNs. Furthermore, the robustness of CNs with parametric uncertainties is discussed. Finally, two examples are given to illustrate the effectiveness of the theoretical results.